C-REACTIVE PROTEIN, INTERLEUKIN-6, SOLUBLE TUMOR NECROSIS FACTOR α RECEPTOR 2 AND INCIDENT CLINICAL DEPRESSION - Chocano-Bedoya, Patricia O. (2014)
BACKGROUND: Despite an extensive literature on the role of inflammation and depression, few studies have evaluated the association between inflammatory biomarkers and depression in a prospective manner, and results are inconclusive. METHODS: We conducted a prospective analysis of blood levels of CRP, IL-6 and TNFα-R2 in 4,756 women participating in the Nurses’ Health Study who donated blood in 1990 and were depression-free up to 1996. Participants were followed between 1996 and 2008 for reports of clinical diagnosis depression or antidepressant use. Additionally, we conducted cross-sectional analyses for CRP, IL-6 and TNFα-R2 and antidepressant use at time of blood draw. RESULTS: After adjustment for body mass index, menopause status, use of anti-inflammatory drugs and other covariates, no significant associations between CRP, IL-6 and TNFα-R2 and incident depression were observed after a follow-up of 6-18 years. However, menopause status appears to modify the association between IL-6 and depression risk. In cross-sectional analyses, TNFα-R2 was associated with antidepressant use (OR=1.96, 95% CI=1.23-3.13, P-trend=0.001), but no significant associations were found for CRP and IL-6. LIMITATIONS: Depression diagnosis was first assessed in 1996, 6 years after blood draw. However the biomarkers have high within-person correlations with measurements 4 years apart. CONCLUSIONS: Blood levels of CRP, IL-6 and TNFα-R2 were not associated with incident depression over a follow-up of 6-18 years. In cross-sectional analyses, antidepressant use may be associated with higher levels of TNFα-R2 but no associations with depression or antidepressant use were observed in the prospective analysis.